Financial performance, gender diversity and corporate environmental performance: the moderating role of firm size - Manfa, Agung; Triyono, Triyono; Bawono, Andy (Politeknik Negeri Madiun, 2024)
Research aims: This study analyzes the relationship between financial performance and gender diversity on the board of directors and environmental performance in non-financial companies, while also examining the moderating role of financial constraints and company size.Design/Methodology/Approach: In this study, panel data analysis was conducted on 75 non-financial companies listed on the Indonesia Stock Exchange that participated in the PROPER program from the Ministry of Environment and Forestry of the Republic of Indonesia from 2018 to 2022.Research findings: The research findings suggest that financial performance and gender diversity are predictors that have a significant impact on the corporate environmental performance variable. However, the study also revealed that company size does not have a moderation effect, except for the level of debt-to-capital ratio, which acts as a quasi-moderation.Theoretical contribution/ Originality: This study offers valuable new insights into the environmental performance of non-financial companies in Indonesia. It specifically assesses their participation in the PROPER program, run by the Ministry of Environment and Forestry. Prior research has not extensively investigated environmental performance within this context. Additionally, the study incorporates financial performance components such as debt-to-capital ratio and sales growth, serving as a proxy for financial performance, in addition to return on assets.Practitioner/Policy implication: This research can be useful for public companies listed on the Indonesia Stock Exchange and provide input to the government, as a reference to increase awareness and environmental management in public companies in Indonesia.Research limitation/Implication: This study gathered data from 2018 to 2022, a period marked by the significant global event, COVID-19 outbreak. Future research should explore how exceptional events, particularly the COVID-19 crisis, influence company performance from the early stages of the pandemic to the recovery period. Such an investigation would produce more accurate outcomes.